A review of pollutants emissions in various pressure gain combustors. (August 2019) - Anand, Vijay; Gutmark, Ephraim
Recent years have witnessed a significant growth in the advancement and study of various unsteady combustors because of the prospective stagnation pressure gain offered by them. The pressure gain combustion produced by this class of combustors is poised to produce a step-change increase in the thermodynamic efficiency of gas-turbine engines. The current manuscript is oriented toward presenting a review on the pollutant emission characteristics of these devices; specifically, studies done so far on wave rotor combustors, pulsejet combustors, pulse detonation combustors, and rotating detonation combustors are evaluated. Because of the inherent fluid dynamic unsteadiness peculiar to pressure gain combustion devices, their emissions behavior is not well understood, and is notably different from the more conventional, steady combustors. The global view provided herein is expected to further the understanding of pressure gain combustion systems and ascertain the practicality of implementing them in real-world applications.